The Protective Potential of Phyllanthus niruri and Corilagin on Gastric Lesions Induced in Rodents by Different Harmful Agents - Klein-Júnior, Luiz C.; da Silva, Luísa Mota; Boeing, Thaise; Somensi, Lincon Bordignon; Beber, Ana P.; Rocha, Jady A. R.; Henriques, Amélia T.; Andrade, Sérgio F.; Cechinel-Filho, Valdir (Planta Medica, 2017)
The gastroprotective effect of the methanol extract of Phyllantus niruri and its main constituent, corilagin, were studied in vivo. The extract (50, 125, or 250 mg/kg, p. o.) inhibited ethanol-induced lesions in rats by 43 % (p < 0.001), 69 % (p < 0.001), and 99 % (p < 0.001), respectively. It also inhibited the formation of indomethacin-induced gastric ulcers in rats by 80 % (p < 0.01), 89 % (p < 0.01), and 97 % (p < 0.01). A decrease in lipid hydroperoxide levels (p < 0.01) and in myeloperoxidase activity (p < 0.05) evidenced a reduction of oxidative damage and neutrophil infiltration in gastric tissues from ulcerated mice using ethanol/HCl. Potent in vitro free radical scavenger activity (IC50 = 0.07) using the DPPH assay was observed. In contrast, the extract (250 mg/kg, i. d.) did not show antisecretory activity in pylorus-ligated rats, and also failed to inhibit the H+,K+-ATPase activity in vitro. However, in pylorus-ligated rats, the extract (50, 125, and 250 mg/kg, i. d.) increased adhered mucus content by 22 % (p < 0.05), 28 % (p < 0.01), and 38 % (p < 0.01), respectively. The involvement of prostaglandins, nonprotein endogenous sulfhydryl compounds, α2-receptors, and endogenous nitric oxide in the gastroprotection elicited by the extract was also evaluated. Finally, corilagin reduced the lesion area of ethanol-induced gastric ulcers in mice by 88 % (30 mg/kg, p. o.; p < 0.001). Based on these results, it has been concluded that P. niruri methanol extract possesses gastroprotective activity by different and complementary pathways, which together promote an improvement in gastric cytoprotection. The presence of corilagin may partially explain the effectiveness of the extract against gastric damage.
Keywords: Phyllanthus niruri; Phyllanthaceae; corilagin; gastric ulcer; prostaglandins; NP-SH compounds; nitric oxide